(untitled) (Research, Society and Development, 2020)
The objective of the work was the elaboration and physical and chemical characterization of a flour product produced from the leaves of umbuzeiro (Spondias tuberosa Arruda) using different drying methods. The experimental procedures consisted of producing flours from the drying of 30 g of leaves in an air circulation oven at 60 °C for 6 h and in a microwave oven (MWO) with 100% power in a single cycle of 2 min and 30 sec. The physical and chemical parameters evaluated both in fresh leaves and in elaborated flours were: water content (WC), water activity, pH, total soluble solids (TSS), crude protein (CP), fixed mineral residue (FMR) and quantification of minerals. The mean value WC of the umbuzeiro leaf in natura (75.06 %) was higher than that found in the flours, which present values ​​close to each other, around 6.00 %, as well as the water activity values, being for in natura leaf (0.987), greenhouse flour (0.330) and MWO flour (0.323). The flours analyzed also showed acid pH, SST values ​​of 7.17 °Brix (drying oven) and 10.27 °Brix (MWO), CP percentage of 9.00% (drying oven) and 8.60% (MWO). In addition to values ​​of FMR (above 12.00%) indicating high mineral content, with emphasis on Ca, K, Mg, Fe, Zn and Cu. The drying process proved to be viable, producing flours with WC values within the current rules and similar yields in the two drying methods employed (23.0%).